Stress-strain state of the system "lumbar spine-sacrum-pelvis" in the conditions of front pelvis - Korzh, Mykola; Staude, Volodymyr; Kondratyev, Andrey; Karpinsky, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The goal: to analyze the stress-strain state of the sacroiliac joints with central, interosseous, dorsal sacroiliac ligaments in normal condition and in the conditions of pelvis tilt in the frontal plane. The methods: for this study virtual model was elected, it was synthesized on the base of CT scan of the lumbar spine, sacroiliac joints (SIJ) and pelvis of 20 patients and MRI of SIJ of 10 patients. Synthesized finite element models of lumbosacral spine and SIJ were loaded on the upper vertebrae LI along the axis of spine with compressive force that was equal to 400 and 2000 N. The results: obtained qualitative picture of the stress-strain distribution in the lumbosacral spine model during pelvic tilt suggest changes in the nature of work in all joints. Pelvis tilt causes additional compression on SIJ that located below (left). Being loaded sacrum provokes additional rotation around SIJ that located below (left). This leads to a shift of conventional axis of rotary pelvis motion forward and down on one side, back and top to bottom — on the other, that was accompanied by a significant increase in the relative compressive deformation of soft tissue structures of SIJ on one side (left). Under the conditions of loading (400 N) combined with pelvis tilt compared to its normal state an increase in tension values in all SIJ ligaments on left side was recorded especially in dorsal, interosseous, cross-iliac and iliac-lumbar ligaments. Relative deformity of hyaline cartilage increased significantly on the left side in interosseous ligaments towards compression direction. An increasing of loading up to 2000 N provided an increased role of sacro-tuber, sacro-spinous, iliac-lumbar ligaments where stresses value increased by 5–10 times. In this situation the values of relative tensile deformations also increases in ventral, interosseous, dorsal, iliac-transverse and iliac-lumbar ligaments on the right side.